2016
DOI: 10.1093/mnras/stw731
|View full text |Cite
|
Sign up to set email alerts
|

Temporal variability of the wind from the star τ Boötis

Abstract: We present new wind models for τ Boötis (τ Boo), a hot-Jupiter-host-star whose observable magnetic cycles makes it a uniquely useful target for our goal of monitoring the temporal variability of stellar winds and their exoplanetary impacts. Using spectropolarimetric observations from May 2009 to January 2015, the most extensive information of this type yet available, to reconstruct the stellar magnetic field, we produce multiple 3D magnetohydrodynamic stellar wind models. Our results show that characteristic c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(55 citation statements)
references
References 40 publications
1
54
0
Order By: Relevance
“…From these studies, authors have found τ Boo A to have a magnetic cycle with polarity reversals in phase with its chromospheric activity cycle of 120 day, as observed for the Sun and 61 Cyg A. Its mass loss rate is not observationally constrained, but MHD simulations of the stellar wind surrounding τ Boo A have been produced by Nicholson et al (2016), using maps from some of the ZDI epochs considered here. We include these results in Figure 5 using blue squares to indicate their derived mass loss rates and angular momentum loss rates.…”
Section: τ Bootis Amentioning
confidence: 85%
See 2 more Smart Citations
“…From these studies, authors have found τ Boo A to have a magnetic cycle with polarity reversals in phase with its chromospheric activity cycle of 120 day, as observed for the Sun and 61 Cyg A. Its mass loss rate is not observationally constrained, but MHD simulations of the stellar wind surrounding τ Boo A have been produced by Nicholson et al (2016), using maps from some of the ZDI epochs considered here. We include these results in Figure 5 using blue squares to indicate their derived mass loss rates and angular momentum loss rates.…”
Section: τ Bootis Amentioning
confidence: 85%
“…To date, no single model (including M15) precisely reproduces the observed mass-rotation distributions, but M15 reproduces the broad dependences of rotation rates on mass and age. The torque in this model has two regimes, either unsaturated where the stellar Rossby 2 Average mass loss rate from the MHD simulations of Nicholson et al (2016).…”
Section: Angular Momentum Loss Prescriptionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Typically used to determine an initial 3D field solution, then a magnetohydrodynamics code evolves this initial state in time until a steady state solution for the wind and magnetic field geometry is attained (e.g. Vidotto et al 2011;Cohen et al 2011;Garraffo et al 2016b;Réville et al 2016;Alvarado-Gómez et al 2016;Nicholson et al 2016;do Nascimento Jr et al 2016). These works are less conducive to the production of semi-analytical formulations, as the principle drivers of the spin-down process are hidden within complex field geometries, rotation and wind heating physics.…”
Section: Introductionmentioning
confidence: 99%
“…Of relevance to this work, in modelling efforts that attempt to explain stellar spin-down, the stellar orientation is usually assumed fixed, and only the spin-aligned component of angular momentum is typically investigated, preventing models from revealing tilting torques. In reality, stellar winds are highly variable and turbulent (Tu & Marsch 1995;Cranmer et al 2015;Kiyani et al 2015), particularly in the young stages (Nicholson et al 2016;Folsom et al 2016). Turbulence and random perturbations will lead to some degree of stochastic variability in the mean angular momentum axis of the wind (Scherer et al 2001).…”
Section: Introductionmentioning
confidence: 99%